The use of inquiry cycle learning to enhance students cognitive abilities on simple harmonic motion - D Hadianti; I Kaniawati; I Hamidah (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The aim of this study was to get an overview of cognitive enhancement in thesubject matter of simple harmonic motion of students who received inquiry cycle learning.There were 20 items test were given to 63 X-grade students from a senior high school inPandeglang. Each item had five options and students had to choose the right one. Method usedin this study was quasi experiment with the randomized pretest-posttest control group design.The result showed that implementation of inquiry cycle learning significantly can furtherenhance students' cognitive abilities (< ḡ > = 0.46) compared to conventional learning (< ḡ > =0.2). From the hypothesis testing, student’s cognitive abilities using inquiry cycle learning wasbetter than student’s cognitive abilities using than conventional learning